Muscle-derived factor alleviated cognitive impairment caused by intestinal ischemia-reperfusion - Yafang Tan; Guo Mu; Feixiang Wang; Xin Fan; Chengjie Yang; Zuan Shi; Yiping Bai; Bingqing Xie; Xuan Yu; Jianguo Feng; Jing Jia; Xiaobin Wang; et al. (Redox Biology)
Intestinal ischemia/reperfusion (II/R) is a common and grave clinical event, with high morbidity and mortality which can cause cerebral dysfunctions. There are no ideal prevention and treatment measures yet. The present study aimed to determine whether muscle-derived factors can alleviate gut-associated cerebral dysfunctions (GACD) following II/R. We measured the tibialis anterior muscle thickness and irisin levels in patients with and without cognitive dysfunction following cardiopulmonary bypass surgery, calculating the correlation between irisin and cognitive impairment. We found that this protective effect is related to muscle-derived irisin. To elucidate the role of irisin in improving GACD, we knocked out FNDC5 to deplete endogenous irisin and supplemented exogenous irisin. Mechanistic insights into irisin's effects on GACD were investigated using in vivo and in vitro models, incorporating techniques such as transmission electron microscopy, protein docking analysis, gene overexpression, and western blotting. FNDC5/irisin deficiency aggravated cognitive impairments, the pro-inflammation microglia activation, oxidative injury, inflammatory response, neuronal apoptosis and ferroptosis, while recombinant FNDC5/irisin reversed the above changes leading to neurostructural and cognition recovery. Mechanistically, thioredoxin-interacting protein (TXNIP) was activated in the II/R-related neuropathology and was deteriorated in FNDC5/irisin knockout mice. Our results highlight the potential of FNDC5/irisin to slow GACD, providing new insights and potential therapeutic strategies for the prevention and treatment of GACD.